Development of enteric coated tablets from spray dried extract of feverfew (Tanacetum parthenium L: ) - Juliana Siqueira Chaves; Fernando Batista Da Costa; Luís Alexandre Pedro de Freitas (Universidade de São Paulo, 2009)
Tanacetum parthenium (feverfew) is an herb that is commercialized worldwide as a therapeutic treatment for migraine. Its pharmacological effect is mainly due to the presence of the sesquiterpene lactone parthenolide as well as of flavonoids. So far, there are no studies on standardization of pre-formulations or phytomedicines containing this herb. The present study aimed at developing a pre-formulation using a standardized spray-dried extract of feverfew and further designing and standardizing enteric coated tablets. In this work, the spray-dried extract of feverfew was evaluated for its parthenolide, santin and total flavonoid content, parthenolide solubility, particle size, tapped density, hygroscopicity, angle of repose and moisture content. Tablets containing the spray-dried extract were tested for their average weight, friability, hardness, and disintegration time. The total flavonoid and parthenolide contents in the spray-dried extract were 1.31 % and 0.76% w/w, respectively. The spray-dried extract presented consistent pharmacotechnical properties and allowed its tableting by direct compression. Tablet properties were in accordance with the proposed specifications. The procedures described herein can be used to prepare and evaluate pre-formulations of feverfew with adequate properties for the development of a high-quality phytomedicine. Tanacetum parthenium (tanaceto) é uma planta medicinal comercializada no mundo todo para tratamento de enxaqueca. Seu efeito farmacológico é creditado principalmente à lactona sesquiterpênica partenolídeo e flavonóides. Até o momento não existem estudos sobre a padronização de pré-formulações ou o desenvolvimento de fitoterápicos com tanaceto. Logo, o objetivo deste trabalho foi obter comprimidos de revestimento entérico a partir de extrato seco e padronizado de tanaceto. Neste trabalho, o extrato seco do tanaceto obtido pelo método de spray drying foi avaliado quanto ao teor de partenolídeo, presença da santina, teor de flavonóides totais, solubilidade do partenolídeo, tamanho de partícula, ângulo de repouso, densidade, análise higroscópica e teor de umidade. A partir do extrato seco obtiveram-se comprimidos que foram revestidos em leito de jorro. Os comprimidos revestidos foram avaliados com relação ao peso médio, friabilidade, dureza e desintegração. O teor de flavonóides totais e de partenolídeo no extrato seco foram 1,31% e 0,76% (p/p), respectivamente. O extrato seco apresentou características farmacotécnicas satisfatórias permitindo a obtenção de comprimidos pelo método de compressão direta. As propriedades dos comprimidos revestidos estão de acordo com as especificações da literatura. Os procedimentos utilizados nesse trabalho podem ser utilizados para obter extrato seco e fitoterápicos de T. parthenium com alto padrão de qualidade.